P412 SCAD: A PLANET TO DISCOVER IN THE UNIVERSE OF ACS. (18th May 2022) - Bertolini, D; Armillotta, M; Bergamaschi, L; Bertelli, M; Di Nicola, F; Sansonetti, A; Donati, F; Pizzi, C; Galiè, N
Abstract: We hereby present the case of a 36–year–old woman with neither a history of cardiovascular disease nor any cardiovascular risk factors. Her only past medical history included a pregnancy from in vitro fertilization and endometriosis treated with progestin. She was admitted to A&E for sudden onset severe stabbing thoracic pain, which occurred at rest and was exacerbated by respiratory efforts, and with spontaneous resolution shortly after admission. While the ECG did not show any signs of ischemic, blood tests revealed a minor rise in inflammatory markers and a significant rise in troponin values, the latter consistent with acute myocardial injury. Given the clinical suspicion of myopericarditis vs acute coronary syndrome, the patient was admitted to cardiac intensive care unit. Bedside echocardiogram performed shortly after admission demonstrated minor pericardial effusion and regional wall motion abnormalities. Thus, the patient underwent urgent coronary angiography, which revealed pronounced vasospasm at the proximal segment of the circumflex artery, which subsided after administration of nitrate, as well as spontaneous dissection of the mid left anterior descending artery extending to its apical branch. Since no high–risk features were identified (single vessel, mid–distal coronary lesion, no symptoms of persistent ischemia), revascularisation was not attempted and conservative therapy was undertaken. During the following days, genetic evaluation and further diagnostic tests were performed to exclude vascular abnormalities in other anatomical sites, which all resulted negative. Outpatient follow–up with CT coronary angiogram demonstrated full patency of left anterior descending artery with spontaneous resolution of the former dissection. This clinical scenario represents an example of an uncommon and thus often overlooked cause of acute coronary syndrome with yet limited evidence on optimal therapeutic and follow–up strategies.